Effects of ageing on seed viability and oil qualities of black cumin cultivars in Ethiopia: Seed viability and oil quality in black cumin - Mengistu, Fekadu Gebretensay; Tilahun, Gizaw Wegayehu (Journal of Spices and Aromatic Crops, 2025)
Seed quality is crucial for the success of crop production, as it affects germination capacity, emergence potential, and seedling growth. This study investigated the impact of extended storage on the germination capacity, oleoresin and essential oil contents of black cumin seeds from three black cumin cultivars in Ethiopia viz. Aden, Dershaye, and Darbera. Seeds were stored for up to three years, and germination studies were conducted using a completely randomized design. Results showed that storage period significantly affected various germination parameters, with a decrease in germination percentage observed with increasing storage period. However, cultivar and the interaction between storage period and cultivar had no statistically significant effect on germination percentage. The study also provides valuable insights into the correlations between different germination indices. Additionally, as black cumin seeds age, their oleoresin and essential oil contents decrease across all three cultivars. Proper seed storage practices are essential in maintaining the germination potential of black cumin seeds, particularly over extended storage periods. Overall, this study provides insights into the impact of extended seed storage on black cumin seed quality and germination potential, highlighting the importance of proper seed management practices to support sustainable crop production.